PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS REALISTIC MATHEMATICS EDUCATION DENGAN SETTING KOOPERATIF TIPE TWO STAY TWO STRAY POKOK BAHASAN SISTEM PERSAMAAN LINIER DUA VARIABEL KELAS VIII - N.L.H, Dzurratul Wasi’ah; Trapsilasiwi, Dinawati; Kristiani, Arika Indah (Kadikma, 2013)
Abstract. The purpose of this research is to know process and result of Development of Mathematics Learning Instruments Based on Realistic Mathematics Education by Setting of Cooperative Two Stay Two Stray for System of Linear Equation in Two Variables topic at eigth grade of Junior High School. Learning instruments development model refers to Plomp models. The research has product namely lesson plan, student book, worksheet, and evaluation test. The products refer to steps of Realistic Mathematics Education and phases of Two Stay Two Stray. Based on validation process and tryout of learning instruments, it can be concluded that the learnig instruments have satisfied of the validaty, practice, and effective criteria. Key Words : Mathematics Learning Instruments, Realistic Mathematics Education, Two Stay Two Stray, System of Linear Equation in Two Variables, Plomp Models.